2013
DOI: 10.7326/0003-4819-158-5-201303050-00002
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Intervention With Stepped Increases in Support to Increase Uptake of Colorectal Cancer Screening

Abstract: Background Screening decreases colorectal cancer (CRC) incidence and mortality, yet almost half of age-eligible patients are not screened at recommended intervals. Objective To determine whether interventions using electronic health records (EHRs), automated mailings, and stepped increases in support improve CRC screening adherence over 2 years. Design 4-group, parallel-design, randomized, controlled comparative effectiveness trial with concealed allocation and blinded outcome assessments. (ClinicalTrials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
260
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(267 citation statements)
references
References 64 publications
5
260
0
2
Order By: Relevance
“…Our results support those of previous studies. 11,[22][23][24] Green et al recently found that an automated mailing led to twice as many persons being screened for colorectal cancers. 23 Adding navigated interventions, such as guided support from a registered nurse, led to further improvements in CRC screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support those of previous studies. 11,[22][23][24] Green et al recently found that an automated mailing led to twice as many persons being screened for colorectal cancers. 23 Adding navigated interventions, such as guided support from a registered nurse, led to further improvements in CRC screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several randomized trials have reported that outreach with FOBT can improve CRC screening rates. [14][15][16][17][18][19][20] However, most were conducted in integrated health plans. 15 , 16 , 18 , 19 Few targeted vulnerable populations cared for in community health centers (CHCs) and other safety net settings.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] However, most were conducted in integrated health plans. 15 , 16 , 18 , 19 Few targeted vulnerable populations cared for in community health centers (CHCs) and other safety net settings. [21][22][23][24] We previously reported that a multifaceted outreach and reminder intervention using mailed FITs increased adherence to annual screening, compared to point-of-care strategies that maximize FIT distribution at clinic visits, for patients due for repeat screening.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] However, CRC screening rates remain suboptimal, even after decades of public health campaigns, public reporting of health plan CRC screening rates, and implementation of visitbased preventive service reminders in electronic health records (EHRs). 4,7,[9][10][11] Therefore, a growing number of private and public health systems are taking a population health perspective and using outreach approaches to promote CRC screening that do not require a face-to-face primary care visit. 12 Active outreach strategies, such as mailed invitations for colonoscopy and/or stool blood testing, can substantially increase screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…12 Active outreach strategies, such as mailed invitations for colonoscopy and/or stool blood testing, can substantially increase screening rates. [9][10][11] The extent to which primary care continues to play an important role in CRC screening in health systems with active population screening outreach programs is unknown.…”
Section: Introductionmentioning
confidence: 99%